Hubungan Dukungan Suami Terhadap Sikap Ibu Untuk Imunisasi Bayi di Puskesmas Peureulak Barat Aceh Timur Tahun 2024 - Elvira Putri; Ester Simanullang; Marliani Marliani (Jurnal Ventilator, 2024)
One reason for the lack of information regarding the economic costs of disability or death and the benefits of immunisation when children in the vicinity are not fully immunised is the discovery of signatures. Many people are confused by the terms vaccination and immunisation. Immunisation is given to neonates as soon as possible because it can avoid primary diseases through vaccination. If the baby receives the right vaccination, he will be protected from dangerous diseases such as disabilities. Basic immunisation of infants and toddlers is a routine immunisation programme as well as an additional immunisation programme to prevent communicable diseases (PD3I) such as tuberculosis, diphtheria, pertussis, tetanus, polio, hepatitis B, and measles to reduce morbidity, mortality and disability in infants and children. BCG once, DPT-HB three times, Polio four times, HB Uniject once, and measles once are the basic vaccines. These vaccines must be given to all infants to prevent diseases from entering the body. The method used was analytical survey research. Exploration of how and why this phenomenon occurs is the goal of the analytical survey research approach.